Strategi Manajemen Pembiayaan dalam Menjamin Keberlanjutan Lembaga Pendidikan Islam - Aris Sutikno; Mahmudah, Mahmudah; Riya Septi Ayana; Siminto, Siminto; Triwid Syafarotun Najah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Financial management is a crucial aspect in ensuring the sustainability of Islamic educational institutions. This article aims to analyze the financial management strategies that can be implemented to ensure the operational continuity of both formal and non-formal Islamic educational institutions. This study uses a literature review method by examining 10 relevant journals on financial management in Islamic educational institutions. The results of this review show that various strategies employed by Islamic educational institutions in managing financing, such as philanthropic fund management, the implementation of a structured budgeting system, and the utilization of digital technology in financial management, play a significant role in enhancing institutional sustainability. Additionally, collaboration between educational institutions and the community is also an important supporting factor. Effective and efficient financing can be achieved through well-planned strategies and continuous monitoring. This study also highlights the importance of innovation in managing financial resources and adapting to the changing needs and challenges of the times. By applying good managerial strategies, Islamic educational institutions can continue to operate effectively and provide a positive impact on the development of education in society.